Gas Prices and Industrial Production Level: Empirical Evidence from Pakistan - Ahmed, Farhan; Kashif, Muhammad; Ahmed, Mumtaz (International Journal of Energy Economics and Policy, 2018)
Pakistan has a vast industrial base which contributes a large portion in economic growth and employs a large population directly and indirectly. The purpose of this research is to examine the shocks of natural gas prices on the industries that use extensive amount of natural gas in their production as raw material and heating source. The industries taken under study are cement, cotton cloth, cotton yarn, glass, nitrogen fertilizer, phosphorus fertilizer, paper and board, sheet iron and synthetic fiber and billet iron. Vector Auto regression (VAR) is applied to check the shocks using monthly data from January 2012 to September 2017, collected from Pakistan Bureau of Statistics (PBS). Impulse response function (IRF), Variance Decomposition and Granger Causality test were executed from VAR estimates to examine gas price shocks on industrial production level in short and long run. Results reveal that gas prices have shocks in short run on all major industries but in long run they seems to stabilize and the effect is minimized. The idea of the study is original and findings help investors, policymakers and regulatory authorities as lots of researches have been undertaken on oil prices shocks and industrial production, while none of research has been conducted on gas prices shocks and industrial production. Keywords: Gas Prices, Impulse Response Function, Industrial Production level JEL Classifications: E30 L95 O13 O14 Q42